2016
DOI: 10.1371/journal.pone.0153285
|View full text |Cite|
|
Sign up to set email alerts
|

Quantification of Dialytic Removal and Extracellular Calcium Mass Balance during a Weekly Cycle of Hemodialysis

Abstract: ObjectivesThe removal of calcium during hemodialysis with low calcium concentration in dialysis fluid is generally slow, and the net absorption of calcium from dialysis fluid is often reported. The details of the calcium transport process during dialysis and calcium mass balance in the extracellular fluid, however, have not been fully studied.MethodsWeekly cycle of three dialysis sessions with interdialytic breaks of 2-2-3 days was monitored in 25 stable patients on maintenance hemodialysis with calcium concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Our data is in keeping with that of several studies, indicating that Ca mass balance in extracorporeal dialysis is the result of a diffusive and a convective component: the former is determined by an integration of dialysate to blood gradients of ionized and complexed Ca, and thus by plasma and dialysate Ca concentrations, the latter by fluid ultrafiltration [26-28]. Thus, great variations may occur between different treatment modes (diffusion-based vs convection-based), prescription (especially dialysate composition), patient characteristics and concomitant therapies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our data is in keeping with that of several studies, indicating that Ca mass balance in extracorporeal dialysis is the result of a diffusive and a convective component: the former is determined by an integration of dialysate to blood gradients of ionized and complexed Ca, and thus by plasma and dialysate Ca concentrations, the latter by fluid ultrafiltration [26-28]. Thus, great variations may occur between different treatment modes (diffusion-based vs convection-based), prescription (especially dialysate composition), patient characteristics and concomitant therapies.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, great variations may occur between different treatment modes (diffusion-based vs convection-based), prescription (especially dialysate composition), patient characteristics and concomitant therapies. For high-volume convective treatments, a great increase in dialysate Ca concentration is needed to counteract convective losses [26]; in BHD, with the use of slightly lower dialysate Ca concentration than ours (i.e., 1.35 mM), a mean 75.6 mg/session negative Ca balance was measured, with great variations between a group of patients with negative balance (mean 170.5 mg/session) and a group with positive balance (mean 126.4 mg/session) [28]. Most of the variation occurred in the complexed rather than ionized Ca balance, whose reasons were not assessed but that speculatively might reside in differences in plasma and dialysate concentrations of anions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that a DCa in the middle of 2.5 and 3.0 mEq/L might be preferable because it gives a mildly positive CaMB, maintains normal SCa and does not stimulate short-term PTH secretion during dialysis [37]. In a more recent study, Waniewski et al [38] observed a mean weekly dialytic removal of 12.8 mmol Ca in 17 patients and a net absorption of 9.5 mmol/week in 8 patients with a DCa of 2.7 mEq/L.…”
Section: Camb In Hemodialysismentioning
confidence: 99%
“…Furthermore, when considering calcium clearance during extracorporeal therapies, changes in serum bicarbonate, pH, and magnesium homeostasis have to be considered. Recently proposed novel calcium kinetic models might prove to be helpful toward a more accurate assessment of calcium balance on HD …”
Section: The Choice Of Dca In Conventional Hdmentioning
confidence: 99%
“…Recently proposed novel calcium kinetic models might prove to be helpful toward a more accurate assessment of calcium balance on HD. [13][14][15] Compelling evidence suggests that calcium mass balance is always positive with a DCa 3.5 mEq/L, negative or neutral with the use of mildly positive calcium balance while maintains optimal serum calcium and PTH levels. 26 Variable calcium balances with the same DCa that have been reported in different studies obviously are accounted for by the variability in baseline serum ionized calcium concentration and the ultrafiltrate volume, but probably also by differences in population characteristics as well.…”
Section: The Choi Ce Of D C a In Conventional Hdmentioning
confidence: 99%